2019
DOI: 10.29333/ejmste/112622
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Peer Effect on Mathematics Anxiety among Secondary School Students of Sokoto State, Nigeria through Photovoice Approach

Abstract: Mathematics anxiety is prevalent in Nigeria where students have a fear of the subject. Much research has been conducted on the level of mathematics anxiety, the differences between the genders, and its relationship with performance. However, little has been done on the factors for mathematics anxiety, and even less on peers' contribution towards mathematics anxiety. The photovoice approach was applied to capture peers' speech and behaviour, which can intensify or minimize mathematics anxiety. The findings reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
0
10
0
4
Order By: Relevance
“…The partial confirmation of hypothesis 1 (statistically significant differences will be reported between the pretest and the posttest for students in the experimental group in both, mathematics learning anxiety and mathematics evaluation anxiety and moderate effect sizes will be reported) was predictable, considering findings from previous research in the field. Recently, although not specifically in the field of mathematics, several authors, such as Knight et al (2018) and Garba et al (2019), documented anxiety improvements through peer tutoring in their respective fields of research. Consequently, it was not surprising that significant improvements were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The partial confirmation of hypothesis 1 (statistically significant differences will be reported between the pretest and the posttest for students in the experimental group in both, mathematics learning anxiety and mathematics evaluation anxiety and moderate effect sizes will be reported) was predictable, considering findings from previous research in the field. Recently, although not specifically in the field of mathematics, several authors, such as Knight et al (2018) and Garba et al (2019), documented anxiety improvements through peer tutoring in their respective fields of research. Consequently, it was not surprising that significant improvements were found.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in spite of the broad range of literature that exists regarding peer tutoring, very few studies have addressed the effects of this methodology on students' mathematics anxiety. Studies by Reyes and Castillo (2015) and Garba et al (2019) have shown promising results but are limited in terms of information, and both suggest further research on the effects of peer tutoring on students' mathematics anxiety. Hence, given the need for students to participate in cooperative and active learning methodologies that lower their mathematics anxiety, and given the proven positive effects of peer tutoring on academic achievement and other psychological variables, a study testing the effects of peer tutoring on students' mathematics anxiety can not only build on the existing literature, but also inform educators on best practices for helping students with mathematics anxiety to improve their performance.…”
Section: State Of the Problem And Need For This Research Studymentioning
confidence: 99%
“…Jadual 3 : Bilangan artikel mengikut tahun penerbitan Donolato et al, 2020;Garba et al, 2020;Kusmaryono et al, 2020;Moliner & Alegre, 2020;Semeraro et al, 2020;Suren & Kandemir, 2020;Trigueros et al, 2020;Wang et al, 2020a;…”
Section: Trend Penyelidikan Faktor Kebimbangan Matematik Dalam Kalang...unclassified
“…Bagi faktor efikasi kendiri, kesemua sembilan kajian yang mengkaji faktor tersebut menunjukkan efikasi kendiri pelajar dalam matematik mempunyai korelasi negatif dengan kebimbangan matematik (Garba et al, 2020;Klee & Miller, 2019;Kusmaryono et al, 2020;Muwonge et al, 2018;Semeraro et al, 2020;Suren & Kandemir, 2020;Wang et al, 2020b;Xie et al, 2019;Živković et al, 2022). Dalam hal ini, pelajar yang menunjukkan keyakinan yang tinggi terhadap kemampuan diri dalam matematik mempunyai kebimbangan matematik yang rendah.…”
Section: Faktor Diri Sendiriunclassified
“…It is a known fact that some primary school students are experiencing a negative attitude toward the math subject (Hambee, 1990;Marhayani, Chang, & Naaranoja, 2019;Raccanello, Brondino, Moè, Stupnisky, & Lichtenfeld, 2018;Yeo, Tan, & Lew, 2015;Zakaria, Zain, Ahmad, & Erlina, 2012). Despite the importance attached to math subject as an academic discipline that students need in the society as explained by Nigeria's National Policy on Education, mathematics is still perceived as a difficult subject for some students in primary schools in Nigeria (Aliyu Garba, Ismail, Osman, & Rameli, 2019). toward an action.…”
Section: Introductionmentioning
confidence: 99%